Negotiation of Chinese Identity in Islamic Education in Public Schools: An Anthropological Study at SMPN 2 Pontianak - Muhardi, Muhardi; Hermansyah, Hermansyah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Amid the increasing complexity of cultural and religious diversity in public schools, maintaining the sustainability of inclusive Islamic values is becoming increasingly urgent. This study aims to examine how Islamic education in multiethnic schools can be a space for identity negotiation between Islam and Chineseness, especially for Chinese students at SMP Negeri 2 Pontianak City. This study uses an anthropological approach with qualitative methods, involving participatory observation and in-depth interviews with 9 informants, consisting of Islamic Religious Education (PAI) teachers, homeroom teachers, Chinese students, and parents. The results show that the practice of Islamic education in this school is carried out through a humanistic approach that is open to diversity, without emphasizing cultural uniformity. Interethnic interactions run harmoniously and contribute to the formation of tolerance values and cross-cultural understanding. Islamic education not only functions as a medium for fostering religiosity, but also strengthens inclusive citizenship identity. This study contributes to the development of a pedagogical model based on local wisdom and universal Islamic values in creating a moderate, fair, and adaptive learning space in a multicultural formal education environment.